2021
DOI: 10.1097/ijg.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Corneal Topography and Biometrics After PRESERFLO Microshunt Surgery for Glaucoma

Abstract: Precis: Glaucoma surgery with PRESERFLO Microshunt shows mild and transient changes in the corneal astigmatism, corneal elevation and biometrics in the early postoperative period. Posterior corneal elevation (PCE) tends to be higher in primary open angle glaucoma (POAG). Purpose:The aim was to determine the changes in the corneal keratometry, astigmatism and elevation, refraction, axial length (AL) and anterior chamber depth and volume after the implantation of the PRESERFLO Microshunt in patients with POAG in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…There is no clear consensus in the peer-reviewed literature on the most efficacious dose and time of MMC to be used during this surgery 22. In our study, 0.2 mg/mL MMC was used for 2 minutes as it has been done in previous studies,10–13,16,20 because the scientific evidence to strongly recommend the use of higher concentrations of MMC in populations of European descent is still scarce. Previously reported data from a multicenter study conducted across multiple European sites by multiple surgeons using 2 different concentrations of MMC (0.2 and 0.4 mg/mL)14 showed that postoperative IOP was similar between both subgroups at 1 and 2 years, however, there was a trend toward a greater IOP reduction with 0.4 mg/mL MMC compared with 0.2 mg/mL MMC after month 6 (the differences were significant only at 6 mo, probably because the study was not powered to assess the effects of different MMC concentrations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear consensus in the peer-reviewed literature on the most efficacious dose and time of MMC to be used during this surgery 22. In our study, 0.2 mg/mL MMC was used for 2 minutes as it has been done in previous studies,10–13,16,20 because the scientific evidence to strongly recommend the use of higher concentrations of MMC in populations of European descent is still scarce. Previously reported data from a multicenter study conducted across multiple European sites by multiple surgeons using 2 different concentrations of MMC (0.2 and 0.4 mg/mL)14 showed that postoperative IOP was similar between both subgroups at 1 and 2 years, however, there was a trend toward a greater IOP reduction with 0.4 mg/mL MMC compared with 0.2 mg/mL MMC after month 6 (the differences were significant only at 6 mo, probably because the study was not powered to assess the effects of different MMC concentrations).…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure for PSM implantation has been previously described by our group. 13 In brief: "All surgeries were performed by the same surgeon (M.I.B. ), with sub-Tenon anesthesia in the inferior-nasal quadrant.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The surgical technique has been previously reported by our group [ 8 ]: https://journals.lww.com/glaucomajournal/Fulltext/2021/10000/Changes_to_Corneal_Topography_and_Biometrics_After.8.aspx .…”
Section: Methodsmentioning
confidence: 99%
“…A side-port incision was created at the end of the surgery to inject 0.1 ml of cefuroxime (1 mg/0.1 ml) into the AC. For combined surgery, the surgical technique was the same and performed at the end of the phacoemulsification and IOL [intraocular lens] implantation procedure” [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…We believe a combination of VEGF suppression and shunt-based procedure would be beneficial to those requiring surgical intervention, with cyclodiode therapy used as an alternative adjunct—showing good IOP reduction (not without its own risks and sight threatening complications). More recent literature on the utilisation of surgical micro-shunts in the treatment of secondary glaucoma has shown promising results [ 35 ]. Further work must be done to look at the potential role of interventional glaucoma and long-term outcomes in patients with neovascular glaucoma.…”
Section: Discussionmentioning
confidence: 99%